Dynamical Optimization of Budget Allocation in Paid Search Advertising - Mrňávek, Vít (2021)
Nowadays, digital marketing has an unshakeable role in the modern marketing mix. Within the online marketing ecosystem, paid search advertising (Sklik, Google Ads, Bing Ads, etc.) is a marketing channel positioned very close to the actual purchase. Therefore, its efficiency is mostly measured in terms of ROI and PPC (paid-per-click). Marketing budgets are still often allocated manually, mostly with simple heuristics settings “to fix obviously bad allocations”, not to achieve optimal portfolio allocation. Moreover, investment allocations are updated quite rarely, not considering seasonal changes in ROI of specific marketing campaigns e.g., umbrellas during rainy days and sunglasses on sunny days. These factors can lead to missing the whole financial potential available in the PPC funnel. The main goal of this work is to explore the possibilities to apply portfolio optimization strategies e.g., Markowitz’s portfolio theory on a real-world PPC account. The focus will be given to allocation in the CSS platform (Comparison Shopping Service) as research so far has been focused mainly on optimizations in Classical Search Engines. Efficiency will be evaluated by comparing potential ROI outcomes of optimized portfolio allocation with the benchmark (current allocations).